2020
DOI: 10.1038/s41598-020-64623-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of MACROD1, MACROD2 and TARG1 expression, localisation and interactome

Abstract: The posttranslational modification ADP-ribosylation is involved in many cellular processes, with distinct roles for poly- and mono(ADP-ribosyl)ation (PAR- and MARylation, respectively). Reversibility of intracellular MARylation was demonstrated with the discovery of MACROD1, MACROD2 and TARG1, three macrodomain-containing enzymes capable of reversing MARylation of proteins and RNA. While the three enzymes have identical activities in vitro, their roles in cells are unclear and published data are partially cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 68 publications
0
29
0
Order By: Relevance
“…Previous studies have demonstrated that reduced latency to fall from the rotarod can be a result of muscle disease [ 76 ], mitochondrial disease [ 77 ] as well as mitochondrial dysfunction induced by ischemic injury [ 78 ]. Therefore, one plausible explanation for Macrod1 KO’s reduced latency to fall from the rotarod, based on the mitochondrial subcellular location of Macrod1 and enrichment in skeletal muscles [ 29 , 33 ] could be, loss of aerobic (mitochondrial) fitness. Indeed, Loss of MACROD1 in RD cells has been shown to cause mitochondrial fragmentation [ 33 ] which might become a problem under continued muscle use and increasing energy demands [ 79 ], such as the rotarod test.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have demonstrated that reduced latency to fall from the rotarod can be a result of muscle disease [ 76 ], mitochondrial disease [ 77 ] as well as mitochondrial dysfunction induced by ischemic injury [ 78 ]. Therefore, one plausible explanation for Macrod1 KO’s reduced latency to fall from the rotarod, based on the mitochondrial subcellular location of Macrod1 and enrichment in skeletal muscles [ 29 , 33 ] could be, loss of aerobic (mitochondrial) fitness. Indeed, Loss of MACROD1 in RD cells has been shown to cause mitochondrial fragmentation [ 33 ] which might become a problem under continued muscle use and increasing energy demands [ 79 ], such as the rotarod test.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one plausible explanation for Macrod1 KO’s reduced latency to fall from the rotarod, based on the mitochondrial subcellular location of Macrod1 and enrichment in skeletal muscles [ 29 , 33 ] could be, loss of aerobic (mitochondrial) fitness. Indeed, Loss of MACROD1 in RD cells has been shown to cause mitochondrial fragmentation [ 33 ] which might become a problem under continued muscle use and increasing energy demands [ 79 ], such as the rotarod test. Certainly, altered mitochondrial structure has previously been linked to muscle fatigue [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations